Dublin Regulation : rebutting the presumption of safe third country - Claudie Ashonie Wilson 1983- (2014)
The Dublin Regulation together with its supporting instruments comprises the Dublin system, a system based on mutual trust and the presumption that all participating states, so-called Dublin states are to be considered as safe third countries due to their recognition of the principle of non-refoulement as a binding obligation. Observing Iceland as a Dublin state, this thesis seeks to examine whether or not an individual subject to removal from Iceland can or should be able to rebut the presumption of safety within the country identified as responsible for examining his or her application for asylum. In so doing, this thesis critically analyses the Supreme Court of Iceland’s assessment in its first two Dublin removal cases SCJ Iceland v Samuel Ugbe and SCJ Okoro Osahon v Iceland. Further, it includes a comparative analysis of Iceland’s Dublin asylum procedures and case-laws with those of the other Nordic states. The thesis is supported mainly by the relevant international, regional and domestic legislation and jurisprudence as well as reports and the writings of scholars. The core findings of the research indicate that while individuals subject to removal from Iceland are not precluded from rebutting the presumption of safety in theory, it is impossible for them to do so in fact. This is mainly attributed to the fact that the Court requires that in order for suffering to meet the threshold for a non-refoulement obligation to be triggered, it must be caused by “systemic deficiency” in the receiving state’s asylum procedures and reception conditions. However, “systemic deficiency” is a stricter condition which although compatible with the EU law is incompatible with that of the ECHR’s well-established standards. Following this conclusion the thesis presents some possible recommendations aimed at addressing this legal fragmentation which in turn will safeguard the fundamental rights of the Dublin returnees. Dyflinarreglugerðin ásamt sínum stuðnings reglugerðum og tilskipunum grundvallar Dyflinarkerfið, sem er ...